Techno-economic viability assessment of a household scale agricultural residue composite Briquette project for rural communities in Nigeria - Kpalo, Sunday Yusuf; Zainuddin, Mohamad Faiz; Abd Manaf, Latifah; Roslan, Ahmad Muhaimin; Nik Ab Rahim, Nik Nor Rahimah (Multidisciplinary Digital Publishing Institute, 2022)
This study evaluated the technical and economic viability of a household scale composite briquette project. The objectives were to assess the quality of briquettes, estimate the cost of production, and determine the feasibility of the project. Briquettes were made from a blend of corncobs and the bark of oil palm trunk using a manual press. Production cost was estimated from the market price of commodities and specific economic indicators were used for feasibility analysis. Sensitivity analysis was performed on some essential input parameters that may affect the profitability of the project. Economic analysis revealed that the unit production cost of the briquettes was USD 0.16 per kg. The net present value was USD 6755.91 from the sale of briquettes at USD 0.26 per kg. An accounting profit is possible once briquette sales are above the break-even point of 7329.8 kg. Households could save about 25% from their per-capita expenditure on fuelwood when briquettes are utilized. Overall, the household briquette project is technically and economically viable in Nigeria. The significance of this study lies in the provision of a piece of baseline information to encourage local bio-energy development and serve as a guide for stakeholders in Nigeria with a potential interest in investing in briquette technology.